Preoperative Radiochemotherapy in Rectal Cancer: Is There an Impact of Oxaliplatin on Pathologic Complete Response and Survival Rates under “Real World“ Conditions? - Grabenbauer, Alexander; Aigner, Thomas; Göbel, Holger; Leibl, Bernhard J.; Lamberti, Christof; Grabenbauer, Gerhard G.; Distel, Luitpold (Cells, 2023)
This study aimed to evaluate the benefit of additional administration of oxaliplatin during fluorouracil-based neoadjuvant radiochemotherapy (nRCT) in terms of pathologic complete remission (pCR), disease-free survival (DFS), and overall survival (OS) in patients with advanced rectal cancer. Between 2006 and 2021, 669 patients (pts) were diagnosed with locally advanced rectal cancer, of whom a total of 414 pts with nRCT were identified and included in the study. A total of 283 pts were treated by nRCT using concurrent chemotherapy with fluorouracil or capecitabine; 131 pts were treated using a combination of fluorouracil or capecitabine and oxaliplatin. Propensity score matching analyses (PSM) with 114 pts in each group were used to balance the patients’ characteristics. OS, DFS, pCR-rate, and potential prognostic factors were compared between the two groups. The median follow-up time was 59.5 weeks in the fluorouracil-group and 43 weeks in the fluorouracil/oxaliplatin group (p = 0.003). After PSM, the pCR-rate (including sustained clinical complete remission) was 27% (31/114 pts) in the fluorouracil/oxaliplatin group and 16% (18/114 pts) in the fluorouracil-group (p = 0.033). There was no difference between these two groups for both 10-year OS and DFS neither before nor after PSM, respectively (OS: 72.6% vs. 55.4%, p = 0.066, and 67.8% vs. 55.1%, p = 0.703, and DFS: 44.8% vs. 46.8%, p = 0.134, and 44.7% vs. 42.3%, p = 0.184). Multivariate analysis identified regression grading according to Dworak grade 4 (HR: 0.659; CI: 0.471–0.921; p = 0.015) and age over 60 years (HR: 2.231; CI: 1.245–4.001; p = 0.007) as independent predictors for OS. In conclusion, the addition of oxaliplatin to fluorouracil during nRCT significantly improved pCR-rate without having an impact on survival.
CRIS-Team Scopus Importer:2023-02-24
Keywords: locally advanced rectal cancer; neoadjuvant radiochemotherapy; oxaliplatin; pathological complete remission; survival; total neoadjuvant radiochemotherapy